Lessons from the Arctic : how Roald Amundsen won the race to the South Pole - Kløver, Geir Olav (Fram Museum, 2017)
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

The significance of petroleum for the South Pole expeditions 1910-1912 - Skarung, Per (The Fram Museum, 2015)
"Inclement weather and lack of fuel was the cause of their deaths".
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; polarhistorie

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Cecilie Skog. Liv Arnesen. Monica Kristensen - Sandberg, Sigri (Polarheltinner : Cecilie Skog, Liv Arnesen, Monica Kristensen, Christiane Ritter, Wanny Woldstad, Ellen Dorthea Nøis, Hanna Resvoll-Holmsen, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; biografier; friluftsliv; kvinner; polarekspedisjoner; polarhistorie

Of reindeer, ponies and automobiles : Roald Amundsen and the Norwegian bid for the South Pole - Turney, Chris (1912 : the year the world discovered Antarctica, 2012)
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Hva er en helt? Kjønn i antarktislitteraturen - Ryall, Anka (Fortid : historiestudentenes tidsskrift, UiO, 2011)
Menneskenes historie i Antarktis er ikke mer enn noen hundre år gammel. De viktigste kildene til denne historien er ekspedisjonsberetningene – en omfangsrik litteratur som kan leses på mange måter, også fra et kjønnsperspektiv.
Keywords: Antarktis; ekspedisjoner; litteratur; polarhistorie

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), norsk oppdager, polfarer og nasjonalhelt. Det første mennesket som fant og seilte gjennom Nordvestpassasjen, og førstemann til å sette fot på Sydpolen. Norges nasjonalarv er en serie gjennomillustrerte bøker som presenterer våre viktigste og mest kjente nasjonale ikoner. De enkeltstående bøkene tar for seg betydelige skikkelser innenfor kunst og litteratur, vitenskap, idrett og samfunnsliv, men også landets mange naturperler, samt sentrale historiske epoker og kulturuttrykk. Hver for seg gir bøkene en oppdatert innføring for lesere som vil gjøre seg bedre kjent med et gitt tema.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav; Cowlishaw, J Basil (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), a Norwegian polar explorer and national hero. The first man to find and sail through the North-West Passage, and the first to set foot on the South Pole. NORWEGIAN HERITAGE is a series of illustrated books about our most important and best-known national icons. The respective titles introduce major personalities from the worlds of art and literature, science and sports, but also the many natural wonders of the country, as well as significant historical periods and cultural expressions. Each book offers an updated introduction to readers who wish to familiarize themselves with a given subject.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

The use and abuse of dogs on Scott's and Amundsen's South Pole expeditions - Murray, Carl (Polar Record, 2008)
In the century since Roald Amundsen and Robert F. Scott led the first and second expeditions to reach the South Pole, commentators have frequently passed judgement on the different means of transport that the two explorers employed. In hindsight, and since he ‘won,’ they have consistently praised Amundsen for using dogs exclusively and criticised Scott for not doing the same. Surprisingly, however, almost no attention has been given to the experience of Amundsen's dogs, whose extreme suffering seems to have vanished into a collective blind spot. Here, with the aim of restoring balance to one part of the vexed historiography of the two explorers, that record is set straight. Amundsen's troubled and contradictory attitude towards his animals is also explored and common misconceptions about Scott's views on the use of dogs for transport are confuted.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie; sledehunder

De fire store : og hvordan de ledet sine menn - Kvam, Ragnar (Gyldendal, 2007)
De satte seg nesten uvirkelige mål. De skulle erobre de siste uoppdagede steder på kloden. Kan deres egenskaper og lederstil fortelle oss hvorfor noen lyktes bedre enn andre? Nansen var først ute. Skituren over Grønland hadde gitt ham ukuelig vågemot: Nå var målet Nordpolen. Siden ville Amundsen samme vei. Britene festet blikket på Antarktis. Først Schackleton, så Scott. Fire menn med store drømmer, sterk vilje, kraftig ego. Som vi vet, skulle ekspedisjonene føre til triumf . og tragedie. I sin nye bok skildrer Ragnar Kvam jr. noen av polarhistoriens mest dramatiske kapitler. Han setter søkelyset på hvem de er, disse fire lederskikkelsene. Hva var det som drev dem? Hvordan ledet de sine menn? Kan deres egenskaper og lederstil fortelle oss hvorfor noen lyktes bedre enn andre? Gjennom fire fortellinger får leseren et fascinerende portrett av "de fire store", av deres evne til å skape motivasjon og lagånd, av deres psykiske utrustning og evne til å takle ekstreme situasjoner. Kvams mål er å kaste nytt lys over det som i siste instans virkelig bestemmer deres måte å lede på deres personlighet.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; polarekspedisjoner; polarhistorie

Christensen, Lars - Mills, William J (Exploring polar frontiers : a historical encyclopedia, 2003)
Keywords: Antarktis; biografier; ekspedisjoner; hvalfangst; polarhistorie; polfarere

Operasjon pingvin : historien om 7070 støtteving - Jansen, Per Einar (Per Einar Jansen, 2002)
Keywords: Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; flyging; flyrekognosering; historie; luftfart; luftforsvaret; luftfotografi; polarhistorie

Den tredje mann : beretningen om Hjalmar Johansen - Kvam, Ragnar (Gyldendal, 1997)
Keywords: Antarktis; Nordmenn; Sydpolsekspedisjonen; biografier; oppdagelsesreiser; polarekspedisjoner; polarhistorie

Norske offentlige samlinger med kulturhistorisk polarmateriale - Barr, Susan (Norsk polarinstitutt, 1994)
Keywords: Antarktis; polarforskning; polarhistorie; polarområdene; polarsamlinger

Before the heroes came : Antarctica in the 1890s - Baughman, Timothy H (University of Nebraska Press, 1994)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; oppdagelsesreiser; polarhistorie

Polarfareren Hjalmar Johansen og Skien - Henriksen, Bredo (B. Henriksen, 1961)
Keywords: Antarktis; Hjalmar Johansen; Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarhistorie

The Attainment of the South Pole - Stefánsson, Vilhjálmur (red.) (Great adventures and explorations : from the earliest times to the present : as told by the explorers themselves, 1947)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Entdeckungen und Ansprüche in der Antarktis - Drygalski, Erich von (Geographische Zeitschrift, 1944)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; internasjonal; polarhistorie; politikk

Polar Ponies: The Forgotten Story of Antarctica’s Meat-Eating Horses - O’Reilly, CuChullaine (The Long Riders Guild Academic Foundation)
While it is now commonly agreed that dog travel in winter conditions is an excellent methodology, abundant evidence demonstrates that this view was not shared by all polar explorers at the beginning of the last century. What has also been overlooked is the simultaneous use of meat-eating horses in trying to reach both the North and South Poles.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie